Geographic accessibility to health facilities predicts uptake of community-based tuberculosis screening in an urban setting - Helen E. Jenkins; Sally Ayuk; Daniela Puma; Meredith B. Brooks; Ana Karina Millones; Judith Jimenez; Leonid Lecca; Jerome T. Galea; Mercedes Becerra; Salmaan Keshavjee; Courtney M. Yuen (International Journal of Infectious Diseases, 2022)
Objectives: Annually, more than 30% of individuals with tuberculosis (TB) remain undiagnosed. We aimed to assess whether geographic accessibility measures can identify neighborhoods that would benefit from TB screening services targeted toward closing the diagnosis gap. Methods: We used data from a community-based mobile TB screening program in Carabayllo district, Lima, Peru. We constructed four accessibility measures from the geographic center of neighborhoods to health facilities. We used logistic regression to assess the association between these measures and screening uptake in one's residential neighborhood versus elsewhere, with quasi-information criterion values to assess the association. Results: We analyzed the screening locations for 25,000 Carabayllo residents from 49 neighborhoods. Pedestrian walk time was preferable to Euclidean distance or vehicular time in our models. For each additional 12 minutes walking time between the neighborhood and the health facility, the odds of residents using TB screening units located in their neighborhoods increased by 50% (95% CI: 26%–78%). Females had 9% (95% CI: 3%–16%) increased odds versus males of using a screening unit in their own neighborhood. Conclusion: Placing mobile TB screening units in neighborhoods with longer pedestrian time to access health facilities could benefit individuals who face more acute access barriers to health care.